PERAN TRUST MEMODERASI PENGARUH PERSONAL SELLING TERHADAP MINAT BELI TERHADAP TAS BEKAS BERMEREK DI FACEBOOK LIVE STREAMING - Qiven Daud; Virgo Simamora (The Indonesian Journal of Public Administration (IJPA), 2022)
In online shopping, trust is an important aspect that influences consumer interest in online transactions. This research is explanatory research that aims to explain the role of trust in moderating the influence of personal selling on the intention to buy second-hand branded bags on Facebook by means of live streaming. The population of this research is all consumers who have bought second-hand branded bags via live streaming on Facebook in the Jabodetabek area. The sampling technique used is a purposive sampling technique that uses certain criteria as a requirement to be a research sample. The data collection instrument used was a questionnaire distributed online via Instagram and WhatsApp. There are 100 respondents in Jakarta who are willing to participate in this study. According to this research, trust is a crucial factor that affects customers' intentions to purchase second-hand branded bags through live streaming on Facebook. On the contrary, this research found that personal selling has no effect on the purchase intention of second-hand branded bags through live streaming on Facebook. Lastly, this study shows that trust makes the effects of personal selling on purchase intention less strong. Key word : trust,  personal selling, purchasing intentions, live streaming.